Students' Perceptions about the Use of Interactive Video and its Effect on Students' Learning Motivation at Elementary School (JIP Jurnal Ilmiah PGMI, 2022)
This study aims to describe students' perceptions of the use of interactive video and its effect on students in learning in grade 5 SDIT Elyaqien. This research method is quantitative. The population in this study were grade 5 students who had implemented learning using interactive video after the post-covid-19 normal era, with a total of 52 students for research and 40 respondents for instrument trials. Data collection techniques through observation, documentation, and questionnaires were tested for validity and reliability. Then it is analyzed using statistical descriptions to answer students' perceptions of using interactive videos. A simple regression analysis is used to respond to the effect of interactive videos on student motivation. The results showed that regarding students' perceptions of using interactive videos, 36 students (69.2%) were included in the good category, and 34 students (65.3%) were in the middle class for learning motivation when using interactive videos. The influence between the variables X and Y show that Fh = 14,353 is greater than Ft = 5.32, and the value of the regression coefficient is .972, which states that for every 1% addition in the use of interactive videos, student motivation increases by 0.505. The use of interactive video-based learning media positively impacts student motivation because it facilitates interaction between teachers and students. So that learning activities will be more effective and can support the deepening of teaching materials.